What Status of the Vasyugan Khanty Vernacular Do Calculations on the LingvoDoc Platform Support from the Point of View of Systemic Morphological Characteristics?; Труды Института системного программирования РАН; Т. 37, № 2 - Vorobyeva V. V. Viktoriya Vladimirovna (2025, 2025)
Текстовый файл